INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON THE INTRODUCTION OF E-BUSINESS AND E-MARKETING IN AGRIBUSINESS - Sanja Stojoska (Faculty of Agricultural Sciences and Food - Skopje, 2023)
The advent of the digital technology, and economic globalization has caused significant changes in the way companies operate, necessitating adjustments to their business and marketing strategies. This study aims to identify and analyze specific internal and external factors that influence the implementation of e-business and e-marketing in small and medium-sized enterprises (SMEs) operating in the agribusiness sector of the Republic of North Macedonia (RSM). The research involved the participation of 76 SMEs, and the findings suggest that innovative marketing solutions and e-marketing activities are not universally embraced by all SMEs, and are instead influenced by various factors, including the nature of the sector, the management's attitude towards e-marketing, and the availability of resources. Although social media marketing is increasingly being employed by SMEs in the agribusiness sector, they often lack systems for tracking and measuring their marketing activities. The role of management in shaping the perception and importance of marketing is a crucial factor, and customer focus is also a significant factor that influences marketing activities. The Covid-19 pandemic has compelled businesses, particularly small and medium-sized enterprises, to adapt to digitalization and evolving consumer needs. The case study of Agro Junikom, a medium-sized enterprise operating in the agribusiness sector in RSM, compared the company's perception and approach to e-business and e-marketing before and after the onset of the pandemic. The comparative analysis of two surveys conducted in 2018 and 2022 showed a significant development in marketing in the digital environment, highlighting the importance of implementing e-marketing to improve company performance when external factors significantly affect business operations. The study's implications are helpful for companies seeking to transition from traditional to digital business models. The findings underscore the need for investing in human, financial, and technological resources to gain support from management and professional teams. The study contributes to the academic literature on e-marketing implementation, providing practical insights for businesses. Successful implementation of e-marketing requires attention to both internal and external factors, ultimately leading to improved company performance.
Keywords: digital technology, factors’ influence, Covid-19, agrobusiness